군 교육에서 교수행동특성이 학습몰입에 미치는 영향 - 손정목(Jung-Mok Sohn); 원유동(You-Dong Won); 강성태(Sung-Tae Kang); 조우성(Woo-Sung Cho); 엄명용(Myoung-Yong Um) (한국콘텐츠학회 논문지, 12(5), 2012)
The purpose of this paper is to investigate which the nature of teacher behavior affects the learning flow in the context of military education. Empirical results show that the leadership of the nature of teacher behavior has a significant effect on three factors of learning flow (flow experience, transformation of time, concentration on task). In addition, the pace of class of the nature of teacher behavior is significantly related to the transformation of time and the concentration on task, and the sense of humor of the nature of teacher behavior significantly affects the concentration on task. The findings provide practical implications on how a military education institution strategically employes the leadership, the sense of humor, and the pace of class in an attempt to select and train instructors. 본 연구의 목적은 군(軍)교육기관의 학습자를 대상으로 교수자의 어떠한 행동특성이 학습몰입에 유의한 영향을 미치는가를 실증적으로 분석하는 것이다. 연구결과 학습몰입의 세 가지 요인(몰입경험, 시간왜곡, 주의집중)에 모두 영향을 미치는 교수행동 특성은 리더십 요인이었다. 또한 교수행동특성 중 수업 진행 속도는 시간왜곡과 주의집중에 유의한 영향을 미치고 있었으며, 유머러스한 교수행동특성은 주의집중 요인에 긍정적 영향을 미치고 있었다. 이러한 결과는 군(軍)교육기관이 교수자의 선발과 훈련에 있어 어떻게 교수자의 리더십, 유머감각, 수업진행 속도를 전략적으로 활용할 수 있는가에 대한 실제적 함의를 제공한다.